2004
DOI: 10.1001/jama.291.1.71
|View full text |Cite
|
Sign up to set email alerts
|

Enthusiasm for Cancer Screening in the United States

Abstract: Context Public health officials, physicians, and disease advocacy groups have worked hard to educate individuals living in the United States about the importance of cancer screening. Objective To determine the public's enthusiasm for early cancer detection. Design, Setting, and Participants Survey using a national telephone interview of adults selected by random digit dialing, conducted from December 2001 through July 2002. Five hundred individuals participated (women aged Ն40 years and men aged Ն50 years; wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

38
464
0
7

Year Published

2004
2004
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 623 publications
(514 citation statements)
references
References 15 publications
38
464
0
7
Order By: Relevance
“…Although the absolute rate of informed choice appears low, against this background we believe the understanding participants demonstrated after a one-off booklet indicates success in communicating complex information about overdetection and other screening outcomes. Widespread public enthusiasm for cancer screening 36,37 can cause resistance to information about harms 38 which have not been well communicated in the past. 39 Mass health education or social marketing campaigns would never rely solely on a single small booklet to ensure effective communication of new information to the public.…”
Section: Discussionmentioning
confidence: 99%
“…Although the absolute rate of informed choice appears low, against this background we believe the understanding participants demonstrated after a one-off booklet indicates success in communicating complex information about overdetection and other screening outcomes. Widespread public enthusiasm for cancer screening 36,37 can cause resistance to information about harms 38 which have not been well communicated in the past. 39 Mass health education or social marketing campaigns would never rely solely on a single small booklet to ensure effective communication of new information to the public.…”
Section: Discussionmentioning
confidence: 99%
“…The reduction in expected participation and perceived parental responsibility was driven by scepticism towards science as well as an understanding of NBS and its effects. These findings are striking given the enthusiasm for science and technology among our respondents, the general public's enthusiasm for screening 28 and their tendency to 'buy into' the messages emanating from scientists, media and commercial interests 'hyping' the promises of science and genomics. 36 Indeed, such enthusiasm was demonstrated in a recent study that reported parental interest in WG/ES-based NBS, based on the perception that WG/ES-based screening would be more accurate.…”
Section: Discussionmentioning
confidence: 80%
“…We asked respondents about their views on parental responsibility to participate in targeted NBS using current technologies and untargeted WG/ES. We adapted a measure of personal responsibility to participate in screening from the cancer context, 28 focusing on parental responsibility, which is appropriate to the infant screening setting. Respondents were asked to choose 'yes' or 'no' to the following question for each technology: 'Would you consider other parents irresponsible if they refused to participate in this type of newborn screening program?'…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations